Prison system in Colombia, human rights and resocialization of women in the El Buen Pastor prison. - Rodríguez Moreno, María Angélica; Gómez Silva, Doris; Bolívar Torres, Emmanuel (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The innumerable complaints and generalised protests presented by women deprived of their liberty, due to the lack of guarantees for the protection of their fundamental rights, overcrowded conditions, lack of budget to provide decent sanitary conditions, evokes and seeks to understand the legislation and the legal framework, in favour of the conservation and preservation of the joint integralities of women in the penitentiary complex in Colombia, more precisely in the prison of El Buen Pastor.It is for this reason that this document develops the different aspects of the condition of being sentenced in prison, under a gender approach and perspectives, and the mechanisms adopted by official institutions to fulfil the function of punishment and the devices that allow an ethical conciliation between equality and community empathy, to address the international recommendations on the mechanisms associated with detention, as a woman, applied to the Colombian legal framework and in accordance with pre-established standards to address the needs to enhance the development and freedoms of all people in the world, without exclusion.